Report of the Preservation Management Summer School Held at The Public Record Office and The British Library, 19th-23rd July 1999 - Mirjam M. Foot (Liber Quarterly: The Journal of European Research Libraries, 1999)
In July 1999 (19th-23rd) one of the first comprehensive summer schools to be organised in the UK on preservation management was held at The Public Record Office, Kew and The British Library, St Pancras, London. Organised by The Public Record Office (PRO) and The Ligue des Bibliothèques Européennes de Recherche (LIBER) in conjunction with The British Library (BL), The European Commission on Preservation & Access (ECPA), University College London (UCL) and the International Council on Archive (ICA), the goal of the Summer School was to introduce key elements of preservation management to archivists and librarians in middle managerial positions, and to give participants practical insights to the problems that arise and the possible solutions, thereby helping delegates to develop and plan preservation policy and practice for their own organisations. In a wider context the aim was to initiate and establish training specific to the requirements of institutions in the increasingly specialist field of preservation management.